Windowsense: a smart convenience window - Yusof, Muhammad Hamizan; Mohd Nasir, Muhamad Izamuddin; Sujuanda, Syarifuddin; Nathan, Shelena Soosay (2024)
Smart windows have garnered significant interest as IoT technology advances, enabling the development of more sophisticated and effective solutions. While traditional windows face challenges related to adverse weather, air quality, and user convenience, this study aims to address these issues by identifying user requirements, developing a smart window prototype, and evaluating its effectiveness in residential areas. To ensure efficient problem-solving, an agile methodology is employed throughout the study. The prototype incorporates three key sensors: a gas sensor, raindrop sensor, and humidity sensor. These sensors enable the smart window to detect and respond to changes in the environment accordingly. The developed smart window demonstrates enhanced convenience and efficiency, leading to high levels of user satisfaction. Looking ahead, the integration of the WindowSense project with other smart home devices and systems holds the potential for further improvements in user efficiency and convenience. This aligns with the study's objectives, and the results obtained provide a strong foundation for future enhancements and integration efforts